Inhibition of the Ubiquitin-Activating Enzyme UBA1 Suppresses Diet-Induced Atherosclerosis in Apolipoprotein E-Knockout Mice - Jiawei Liao; Xiaolei Yang; Qiuyue Lin; Shuang Liu; Yunpeng Xie; Yunlong Xia; Hui-Hua Li (Journal of Immunology Research)
Background. Ubiquitin-like modifier activating enzyme 1 (UBA1) is the first and major E1 activating enzyme in ubiquitin activation, the initial step of the ubiquitin-proteasome system. Defects in the expression or activity of UBA1 correlate with several neurodegenerative and cardiovascular disorders. However, whether UBA1 contributes to atherosclerosis is not defined. Methods and Results. Atherosclerosis was induced in apolipoprotein E-knockout (Apoe-/-) mice fed on an atherogenic diet. UBA1 expression, detected by immunohistochemical staining, was found to be significantly increased in the atherosclerotic plaques, which confirmed to be mainly derived from lesional CD68+ macrophages via immunofluorescence costaining. Inactivation of UBA1 by the specific inhibitor PYR-41 did not alter the main metabolic parameters during atherogenic diet feeding but suppressed atherosclerosis development with less macrophage infiltration and plaque necrosis. PYR-41 did not alter circulating immune cells determined by flow cytometry but significantly reduced aortic mRNA levels of cytokines related to monocyte recruitment (Mcp-1, Vcam-1, and Icam-1) and macrophage proinflammatory responses (Il-1β and Il-6). Besides, PYR-41 also suppressed aortic mRNA expression of NADPH oxidase (Nox1, Nox2, and Nox4) and lesional oxidative stress levels, determined by DHE staining. In vitro, PYR-41 blunted ox-LDL-induced lipid deposition and expression of proinflammatory cytokines (Il-1β and Il-6) and NADPH oxidases (Nox1, Nox2, and Nox4) in cultured RAW264.7 macrophages. Conclusions. We demonstrated that UBA1 expression was upregulated and mainly derived from macrophages in the atherosclerotic plaques and inactivation of UBA1 by PYR-41 suppressed atherosclerosis development probably through inhibiting macrophage proinflammatory response and oxidative stress. Our data suggested that UBA1 might be explored as a potential pharmaceutical target against atherosclerosis.